If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x+5)(x-1)=(x+2)(x+1)
We move all terms to the left:
(2x+5)(x-1)-((x+2)(x+1))=0
We multiply parentheses ..
(+2x^2-2x+5x-5)-((x+2)(x+1))=0
We calculate terms in parentheses: -((x+2)(x+1)), so:We get rid of parentheses
(x+2)(x+1)
We multiply parentheses ..
(+x^2+x+2x+2)
We get rid of parentheses
x^2+x+2x+2
We add all the numbers together, and all the variables
x^2+3x+2
Back to the equation:
-(x^2+3x+2)
2x^2-x^2-2x+5x-3x-5-2=0
We add all the numbers together, and all the variables
x^2-7=0
a = 1; b = 0; c = -7;
Δ = b2-4ac
Δ = 02-4·1·(-7)
Δ = 28
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{28}=\sqrt{4*7}=\sqrt{4}*\sqrt{7}=2\sqrt{7}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-2\sqrt{7}}{2*1}=\frac{0-2\sqrt{7}}{2} =-\frac{2\sqrt{7}}{2} =-\sqrt{7} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+2\sqrt{7}}{2*1}=\frac{0+2\sqrt{7}}{2} =\frac{2\sqrt{7}}{2} =\sqrt{7} $
| 3x/12=69 | | 9^x-4x3^x-1+27=0 | | 5x+4=203x | | x*360/3400=9 | | x360/3400=9 | | 11x-3=68 | | 3x+2(x-1)=2x+4 | | 7X^2-100x-60000=0 | | 7X^2-100x-6000=0 | | 7X^2-100x+6000=0 | | X^2-100x-6000=0 | | 6x+2=4x–12 | | a+(3/2a)+2a+6a=1400 | | 203x=2x-5 | | a+3/2a+2a+6a=1400 | | m^2-3m+2.25=0 | | 6x2-30=0 | | 23x-17=19+x | | 9x^2-19x-6=65 | | 6d+4d+3d+d=1400 | | x-19=2x+14 | | 7x=3x-1 | | 4x+14-3x=17x | | 7x=3x12 | | (x)=6⋅x+3 | | 4(x-6)=-18 | | -5(-4u+6)-u=4(u-6)-9 | | y=8+2/3 | | 3x+8=-x+9 | | 2(x+9)=-5(3x-2)+3x | | (14+-1y)+4y=26 | | -5(2u-1)+8u=1+2(5u-3) |